2020
DOI: 10.1016/j.bbmt.2019.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for Autoimmune Cytopenias after Allogeneic Hematopoietic Cell Transplantation in Children

Abstract: of autoimmune cytopenia (AIC) after allogeneic hematopoietic cell transplantation (HCT) is a serious complication requiring urgent intensification of immunosuppressive therapy. The pathophysiology and predictors of AIC are not completely understood. In this retrospective cohort analysis of 380 pediatric patients, we evaluated the incidence, outcomes, and related various variables, including immune reconstitution markers to AIC. Three hundred eighty patients (median age, 7.4 years; range, .1 to 22.7) were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 22 publications
0
36
1
1
Order By: Relevance
“…Curiously, this is inconsistent with prior reports. 16,22,24 Likewise, in the prior literature, 20,25 viral reactivation has been suggested to be a trigger in AICs, but this was not observed in our cohort.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Curiously, this is inconsistent with prior reports. 16,22,24 Likewise, in the prior literature, 20,25 viral reactivation has been suggested to be a trigger in AICs, but this was not observed in our cohort.…”
Section: Discussioncontrasting
confidence: 50%
“…This is comparable to the incidences of 2.1%-7.8% previously reported in similar pediatric patient populations. 4,5,8,20,21 The association of nonmalignant disease with the development of AIC has been widely reported. 4,7,[20][21][22][23] Because prior studies identified primary nonmalignant disease and unrelated donor as risk factors for post-transplant AIC, we chose to match our control group based on these variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autoimmune cytopenias for patients with secondary immunodeficiency, such as after allogeneic HSCT or after organ transplantation, are among the most difficult to diagnose and treat. Recent studies and reviews that address this topic specifically [29][30][31] provide more in-depth guidelines than this present work focusing on SIC in primary immunodeficiencies. In brief, autoimmune cytopenias in secondary immunodeficiencies such as post-transplantation settings may be caused by a complex mix of underlying pathomechanisms such as imbalanced immune reconstitution with preponderance or insufficient elimination of autoreactive T-or B-cell clones, calcineurin inhibitor-facilitated skewing of the immune system, drug-induced thrombotic microangiopathy or sinusoidal obstruction syndrome, and virustriggered conventional autoimmune reactions, to list a few.…”
Section: Scenario 4: Autoimmune Cytopenia Newly Arising In a Patient mentioning
confidence: 99%
“…Furthermore, there are no clear guidelines on the diagnosis and management of IMC after transplantation. Since IMD itself appears to be an independent risk factor for IMC or has a relatively higher incidence of IMC [10][11][12][13][14], a multinational panel of physician experts in the treatment of IMD was convened, with the primary aim to identify the strategies for effective and timely diagnosis and develop a management strategy for IMC in this patient population. The panel included experts in HCT for IMDs from centers with experience in treating these disorders as well experts in nonmalignant disorders and transplant immunology.…”
Section: Introductionmentioning
confidence: 99%